Future Directions About Keloid Scars Based on Pathogenesis and Therapies - Zhang G; Liu Z; Li Z; Xu Y (Dove Medical Press, 2024)
Guiyun Zhang,1 Zhe Liu,1 Zhen Li,2 Yangchun Xu1 1Department of Dermatology, The Second Hospital of Jilin University, Changchun, 130041, People's Republic of China; 2Department of Medical Administration, The Second Hospital of Jilin University, Changchun, 130041, People's Republic of ChinaCorrespondence: Yangchun Xu, Department of Dermatology, The Second Hospital of Jilin University, No. 218 Ziqiang Street, Nanguan District, Changchun, 130041, People's Republic of China, Tel +86-431-81136244, Email Xuyc@jlu.edu.cnAbstract: Keloids are pathologic scars that pose a significant functional and cosmetic burden. While the literature on keloid management continues to expand, the absence of standardized guidelines or treatment protocols endorsed by academic governing bodies remains a significant challenge. The pathogenesis of keloid scars is not fully elucidated. This review delves into the intricate pathogenesis of keloids, exploring the molecular and cellular mechanisms underlying their formation. Conventional therapies are analyzed in-depth considering their efficacy and limitations, including surgical excision, pharmacotherapies, radiotherapy, cryotherapy, silicone-based product, pressure therapy, and light-based therapy. The emergence of novel therapeutic approaches is discussed, including pharmacotherapies, physical therapies, and biological therapies, shedding light on their potential in treating keloid scars. We also contemplate future directions in the field, encompassing the application of targeted therapies, gene-editing tools, tissue engineering, and regenerative medicine, together with psychosocial support and patient education. In synthesizing current knowledge, scrutinizing therapeutic modalities, and envisioning future avenues, this review aims to provide a comprehensive reference for clinicians, researchers, and stakeholders engaged in the intricate field of keloid management.Keywords: keloid scars, pathogenesis, therapies